Acute distal biceps tendon ruptures: anatomy, pathology and management - state of the art. Issue 5 (27th August 2020) - Kruger, Neil; Phadnis, Joideep; Bhatia, Deepak; Amarasooriya, Melanie; Bain, Gregory Ian
Abstract : All patients with acute complete distal biceps tendon ruptures who are not low demand or medically unfit to proceed with surgery are offered operative repair. This restores arm shape, supination strength and function, and decreases their cramping symptoms. Surgical repair technique varies significantly depending on location and training centre. Nuances in technique and appropriate implant selection need to be noted in order to achieve a strong repair allowing early active range of motion. Intimate knowledge of distal biceps tendon anatomy is key to avoid complications associated with the different approaches. The cumulative body of evidence on complications, coupled with knowledge of the different biomechanical construct strengths of the alternative methods of fixation, points to the use of the cortical button technique without the addition of an interference screw. Subtle variations in drill hole positioning on the bicipital tuberosity secures either an anatomic or non-anatomic repair. Anatomic repair results in greater supination peak torque and fatigue strength, and in greater flexion fatigue strength. It is advisable to perform an anatomic repair in elite athletes or those patients who significantly rely on supination strength and endurance for their livelihood. A universal postoperative protocol is suggested for all repairs.